2010
DOI: 10.1007/s12126-010-9074-z
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Aging Project: Training Outcomes and Efficacy from a Randomized Field Trial

Abstract: This study examined whether training provided to adults age 60+ would increase the use of information and communication technologies (ICTs), such as email and the Internet, and influence participants' social support and mental health. Participants were randomly assigned to an experimental (n=45) or a control group (n=38). The experimental group participated in a six-month training program. Data were collected before, during, and after training on outcomes related to computer use, social support, and mental hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(92 citation statements)
references
References 45 publications
(58 reference statements)
1
89
1
Order By: Relevance
“…Such emotions, in turn, frequently lead to a decline in continued use. Indeed selfefficacy as a predictor of seniors' motivation and /or future patterns of internet use has now been well established (Chu 2010;de Ruiter 2002;Dickinson et al 2005;Kambouri et al 2006;Woodward et al 2011). This may also help to explain why a senior's previous training or educational achievements have been found to impact upon their willingness to begin using the internet.…”
Section: Attitudinal Impedimentsmentioning
confidence: 98%
See 4 more Smart Citations
“…Such emotions, in turn, frequently lead to a decline in continued use. Indeed selfefficacy as a predictor of seniors' motivation and /or future patterns of internet use has now been well established (Chu 2010;de Ruiter 2002;Dickinson et al 2005;Kambouri et al 2006;Woodward et al 2011). This may also help to explain why a senior's previous training or educational achievements have been found to impact upon their willingness to begin using the internet.…”
Section: Attitudinal Impedimentsmentioning
confidence: 98%
“…Chu's findings also suggested that whilst positive support could improve the behavioural outcomes of older adults searching, problematic support reduced optimal outcomes (2010). There are numerous papers, in fact, that similarly discuss this connection between the type of training and support and the likelihood of senior participants becoming independent and effective search engine users (Cody et al 1999;DeGraves and Denesiuk 2000;Dickinson et al 2005;Woodward et al 2011).…”
Section: Issues Of Training and Supportmentioning
confidence: 99%
See 3 more Smart Citations